STRATEGI KOMUNIKASI PEMASARAN PT. CIPUTRA SYMPHONY MELALUI AKTIVITAS PERSONAL SELLING UNTUK MENINGKATKAN PENJUALAN PERUMAHAN CITRALAND PEKANBARU - Silvia, Mega; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The population increase of Pekanbaru City is very important for housing demand. Property businesses invest to building housing. Increasing home business is also followed by competition from various developers, competitive prices, quality, quantity of developers, and strategic location. Property entrepreneurs must have creative promotional ideas to attract customers. Based on that?s many property companies in Pekanbaru City, establishing Citraland Housing in Pekanbaru can be used to increase sales value. Therefore researchers are interested in researching with the objectives of the Marketing Communication Strategy of PT. Ciputra Symphony with Personal Selling Activities to increase the sales value of Citraland Pekanbaru Housing.This research is using qualitative methods. It?s collecting data from the field with observation, interviews, and documentation. The research subjects are 1 marketing head, 3 marketing people, 3 customers and 2 prospective customers of Citraland Pekanbaru. It was chosen based on purposive sampling technique and using analysis techniques of interactive data, while data validity checking techniques with extended participation and triangulation.The results of this research first, prospecting is a promotional activity such as exhibitions, canvasing and collaborating with bank partners. Second, an approach to know how start communication to make a good relationship, as well as inviting prospective customers and customers to a Galadinner event and gathering Citraland Pekanbaru Housing. Third, presentation and demonstration are making sales presentations. Fourth, handling objection used with a positive approach, found hidden rejection and asking buyer to explain each reason of rejection. Fifth is closing, Citraland helps the process of purchase administration.